2005
DOI: 10.1042/cs20040326
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular risk parameters in men with ankylosing spondylitis in comparison with non-inflammatory control subjects: relevance of systemic inflammation

Abstract: Men with AS (ankylosing spondylitis) are at elevated risk for CHD (coronary heart disease) but information on risk factors is sparse. We compared a range of conventional and novel risk factors in men with AS in comparison with healthy controls and, in particular, determined the influence of systemic inflammation. Twenty-seven men with confirmed AS and 19 controls matched for age were recruited. None of the men was taking lipid-lowering therapy. Risk factors inclusive of plasma lipids, IL-6 (interleukin-6), CRP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
74
0
7

Year Published

2007
2007
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 129 publications
(88 citation statements)
references
References 23 publications
7
74
0
7
Order By: Relevance
“…We acknowledge that the effects of TNF modulation in patients with PsA and psoriasis may potentially differ from its effects in patients with other autoimmune diseases. However, the range of risk factor abnormalities at baseline and the association of CRP with many parameters were generally similar to findings in RA and related conditions (e.g., ankylosing spondylitis) (15). We also acknowledge that determination of fasting triglyceride and insulin levels would have been advantageous, but it is noteworthy that all other lipids and other measured risk factors are not appreciably altered by nonfasting status.…”
supporting
confidence: 72%
See 1 more Smart Citation
“…We acknowledge that the effects of TNF modulation in patients with PsA and psoriasis may potentially differ from its effects in patients with other autoimmune diseases. However, the range of risk factor abnormalities at baseline and the association of CRP with many parameters were generally similar to findings in RA and related conditions (e.g., ankylosing spondylitis) (15). We also acknowledge that determination of fasting triglyceride and insulin levels would have been advantageous, but it is noteworthy that all other lipids and other measured risk factors are not appreciably altered by nonfasting status.…”
supporting
confidence: 72%
“…The evidence for causal links between these pathways is stronger in the context of high-grade inflammation, which occurs in a variety of autoimmune inflammatory conditions such as RA or ankylosing spondylitis (1,15). Of specific interest to the present study, psoriasis has recently been reported to confer an independent risk of myocardial infarction, with the relative risk being greatest in young patients with severe psoriasis (16).…”
Section: Discussionmentioning
confidence: 82%
“…Although specific CV disorders (valvular disease and conduction disturbances) occur more frequently in AS (4,5), accelerated atherosclerotic disease probably contributes to the increased CV risk as well (6,7). Atherosclerosis is a multifactorial process, but its most well-established risk factor is dyslipidemia.…”
mentioning
confidence: 99%
“…Inflammation deteriorates the lipid profile, as characterized by low HDL, total cholesterol, and Apo A-I levels and increased levels of low-density lipoprotein cholesterol (LDL-c), triglycerides, and Apo B. Indeed, several investigators have reported that patients with inflammatory rheumatic diseases have a deteriorated lipid profile (4,6,(8)(9)(10).…”
mentioning
confidence: 99%
“…Although the association between smoking and CV risk in RA is less significant than in the general population [Symmons and Gabriel, 2011], a higher prevalence of smoking is well-established in RA, SA, and PsA compared with controls [Boyer et al 2011;Divecha et al 2005;Favato, 2008;Peters et al 2004]. Hypertension is common in RA but it is not clear whether its incidence differs from that of the general population [Boyer et al 2011;Liao and Solomon, 2013;Protogerou et al 2013].…”
Section: Standard CV Risk Factorsmentioning
confidence: 99%